Evidence is stronger than you think: a meta-analysis of vitamin C use in patients with sepsis - Li, Jing (Critical care (London, England), 2018)
Two recent publications by Sheikh and Horner and Teng et al. reviewed studies on incorporating vitamin C to treat septic patients; however, a meta-analysis was not offered in either report. This commentary extends both reviews by integrating a meta-analysis and sharing aggregated results. Pooled analyses demonstrated a marked reduction in mortality and duration of vasopressor administration in the group with the use of vitamin C.